Association between sustained virological response and clinical outcomes in patients with hepatitis C infection and hepatocellular carcinoma. Issue 19 (7th July 2022) - Parikh, Neehar D.; Mehta, Neil; Hoteit, Maarouf A.; Yang, Ju Dong; John, Binu V.; Moon, Andrew M.; Salgia, Reena J.; Pillai, Anjana; Kassab, Ihab; Saeed, Naba; Thyssen, Emil; Nathani, Piyush; et al.
Abstract : Background: Sustained viral response (SVR) improves survival for patients with hepatitis C (HCV) and hepatocellular carcinoma (HCC) after curative treatment; however, the benefit of SVR in those with active HCC with a significant competing risk of mortality is unknown. This study aimed to evaluate the association between SVR and outcomes in patients with active HCC. Methods: The authors performed a multicenter, retrospective cohort study including consecutive adults with HCV cirrhosis and treatment‐naive HCC diagnosed between 2014 and 2018. Patients were stratified into two groups: active viremia ( n = 431) and SVR before HCC diagnosis ( n = 135). All patients underwent nonsurgical therapy as their initial treatment and were followed until liver transplantation, last follow‐up, or death. The primary outcome was incident or worsening hepatic decompensation within 6 months and the secondary outcome was overall survival. All analyses used inverse probability of treatment weights (IPTW) to account for differences between the nonrandomized cohorts. Results: Post‐SVR patients had significantly lower odds of hepatic decompensation compared to viremic patients (odds ratio [OR], 0.18; 95% confidence interval [CI], 0.06–0.59). Results were consistent among subgroups of patients with Child Pugh A cirrhosis (OR, 0.22; 95% CI, 0.04–0.77), Barcelona Clinic Liver Cancer stage B/C HCC (OR, 0.20; 95% CI, 0.04–0.65), and those receiving nonablative HCC therapies (OR, 0.21; 95% CI, 0.07–0.67). However, in IPTW multivariable Cox regression, SVR was not associated with improved survival (hazard ratio, 0.79; 95% CI, 0.56–1.12). Conclusions: Patients with HCV‐related HCC and SVR are less likely to experience hepatic decompensation than viremic patients, suggesting patients with HCC who are undergoing nonsurgical therapies may benefit from DAA treatment. Abstract : Hepatitis C virus‐related hepatocellular carcinoma remains prevalent in clinical practice, however, whether treatment of hepatitis C improves outcomes is unknown. The authors have shown an association between hepatitis C sustained virological response and decreased risk of hepatic decompensation in patients with hepatocellular carcinoma, across stages of disease and types of therapy received. See also pages 000–000.